Epidemiologic, Clinical Features of Scrub Typhus in Patients in Nakhornping Hospital, Chiang Mai, Thailand - Krittigamas, Pornsuda; Kanjanavanit, Suparat; Ananthanavanit, Maneerat (Journal of Health Science of Thailand, 2017)
Scrub typhus, a potentially fatal rickettsia infection, is common in Asia. Although serologic surveys suggested that as many as one-fourth of cases of scrub typhus might be in children, very few reports on childhood scrub typhus are available in the medical literature. The objective of this retrospective descriptive study was to investigate the clinical, laboratory and epidemiologic characteristics of pediatric patients with scrub typhus and comparable clinical manifestation between who have positive PCR test and negative for scrub typhus and murine typhus. From January 1, 2004 to December 31, 2005, all pediatric patients at Nakornping Hospital who had clinical diagnosis for scrub typhus were enrolled. Fifty nine Thai children with clinical diagnosis for scrub typhus were studied while 29 children definitely diagnosed by PCR (median age 6 years, range 1-15years, male: female ratio 1.4:1). Most patients lived in Tambon Pong Yaeng, Amphoe Mae Rim, Chiang Mai province. Most were diagnosed during the rainy months of June to December. They were presented with subacute fever range 4-14 days (89.7%). Common physical signs included eschar (55.2%), hepatomegaly (34.5%), tachypnea (27.6%), cough (24.1%), diarrhea (24.1%) and abdominal pain (7%). Eschar is specific for scrub typhus (p<0.001). Children who have PCR positive for scrub typhus have normal blood leucocyte counts but thrombocytopenia. All patients responded well to doxycycline or chloramphenicol resulting in only two deaths. The presence of fever, eschar,hepatomegaly were helpful in the diagnosis of scrub typhus (positive predictive value 100%, negative predictive value 57.3%). Complications included pneumonitis and septic shock.